Application of the Kirkpatrick model in the pediatric surgical nurse specialist training program (柯氏模型在小儿外科专科护士培训中的应用) - CHEN Qiqi (陈琪琦); LI Gefang (李各芳); LIU Rong (刘荣) (中西医结合护理)
Objective To apply the Kirkpatrick model in pediatric surgical nurse specialist training program, and comprehensively evaluate its effectiveness, continuously refine the training framework, and ultimately improve training quality. Methods Guided by Kirkpatrick Model, this study conducted a comprehensive evaluation of training effectiveness across four levels (reaction, learning, behavior, and results) through questionnaire surveys and interviews. Based on analysis of evaluation outcomes, reflective summarization and program improvements were implemented. Results A Kirkpatrick Model-based training program was developed and delivered through three training sessions. Implementation outcomes revealed: Reaction-level evaluation demonstrated high satisfaction among trainees across all three sessions; Learning-level assessment indicated significantly higher theoretical test scores post-training compared with pre-training baselines (P＜0. 05); Behavior-level feedback from both clinical instructors and trainees confirmed improvements in professional attitudes and job competencies; Results-level analysis showed substantial enhancement of core competencies among specialist nurses during later training phases. Conclusion The Kirkpatrick model-based specialist nurse training program effectively facilitates the application of training outcomes, guides program optimization, and continuously improves training quality for specialist nurses. (目的 将柯氏模型应用于小儿外科专科护士培训中并全面评价培训效果, 完善专科护士培训方案, 提高培训质量。方法 以柯氏模型为指导, 从反应层、学习层、行为层与结果层4个层面, 运用问卷调查法、访谈法等依次对培训效果进行相关评价, 并根据评价进行反思、总结、整改。结果 构建了基于柯式模型的培养模式, 共开展了3期培训班。实施结果显示, 反应层评价显示3期学员对培训满意度均有较高的满意度; 学习层评价显示3期学员的理论成绩评分均高于培训前(P＜0. 05); 行为层评价显示临床带教老师和学员均认为培训后, 学员的专科护士行为态度及岗位能力均有所提高; 结果层评价显示学员在培训后期专科护士的核心能力均有较高的提升。结论 基于柯式模型构建的专科护士培训班, 有助于促进培训成果应用, 引导培训计划修正, 不断提高专科护士培训质量。)